Digital Competence of Vocational Teachers in the Industrial Era 4.0: Literature Analysis with the PRISMA Approach - Gin Gin Jeni Purnama; Tuti Suartini; Saripudin Saripudin (Universitas Ahmad Dahlan, 2026)
Rapid technological advancements have transformed many aspects of education, including the vocational learning environment. Teachers in vocational schools are expected to master digital skills to support the learning process and meet the demands of the evolving workforce. However, the digital competence of vocational educators remains uneven and often underdeveloped in many regions. This study aims to systematically review current research on teachers’ digital competence in vocational education. The study focuses on identifying key themes, trends, and challenges discussed in the current literature to provide a clearer understanding of the field. The method used in this study is a Systematic Literature Review. A total of 1,250 articles were identified through database searches and manual references. After removing duplicates and irrelevant studies, 10 articles were selected for in-depth analysis. The selection process followed the PRISMA framework to ensure transparency and reliability. The study findings revealed that vocational teachers are increasingly aware of the need to develop digital skills. However, many still struggle due to limited access to digital devices, lack of training opportunities, and low institutional support. The most frequently emphasized competencies include digital pedagogy, the ability to use educational technology, and the ability to create digital learning content. In conclusion, improving digital competence among vocational teachers requires more than individual efforts. Strong institutional support, regular training programs, and stronger links between schools and industry are needed.